Groundwater origami: Folding paper models to visualize groundwater flow - Lowry, Christopher S.; Dunkle, Kallina M.; Kairies-Beatty, Candace L.; Arslan, Sebnem; Stahl, Mason; Bogie, Nathaniel; Cuthbert, Mark O. (Frontiers in Environmental Science, 2022)
The training of geological scientists, more so than any other natural science, is dependent on how students learn to visualize and interpret complex three-dimensional problems at scales from micrometers to kilometers over time scales that span from seconds to centuries. Traditionally, our classrooms are at a disadvantage due to our standard two-dimensional use of whiteboards or slide decks. We are at an even bigger disadvantage when courses go to online education. While computer simulations and three-dimensional visualizations are used, they can lack the flexibility for students to perform free-form exploration. The novelty of this research is in the use of paper aquifer models and their implementation across seven academic institutions to provide three-dimensional physical examples for students to visualize subsurface geologic structure and quantify fluid flow through porous media. Students can cut, fold, and build three-dimensional hydrologic problems at home or in the classroom. Our methodology allows students to physically rotate their aquifer models to visualize cross-sectional areas, layer thicknesses, heterogeneity, and confining units. These foldable paper models provide a low barrier of entry for students to understand and quantify the relationships between water levels and geologic structure. Our experience using these models in both in-person and online classrooms highlights the advantages and disadvantages of these models. Results, although mostly anecdotal, suggest the paper models improve students’ learning and enhance their engagement with the material. The formal evaluations of pre- and post-model implementation show that low-scoring students had the most significant gains after being introduced to the paper aquifer models. At the same time, there was no change in the number of students in the highest scoring group. Our experience in the classroom points to new opportunities to engage with remote learners and tools for supporting flipped classroom activities. Our vision for the paper aquifer models is to provide the hydrologic community with an additional tool to help bridge the virtual classroom gap, engage students, and help them develop mastery of three-dimensional problem-solving.